Tomato Extract as an Immunomodulator in Mice (Mus musculus) Infected with Plasmodium berghei - Iswari, Retno Sri; Yuniastuti, Ari; Dafip, Muchamad (Pakistan Journal of Nutrition, 2016)
To prevent malaria, it is necessary to increase the immune response in the body and reduce disease severity by eradicating the parasites within the body. Tomato (Lycopersicum esculentum Mill) is believed to be able to increase the immune response to combat infection. The current study examined 5 different treatment conditions and each treatment was repeated 6 times. The negative control group (K-) was given standard nourishment, while the positive control group (K+) received both standard nourishment and chloroquine treatment. Groups P1, P2 and P3 were given standard nourishment, as well as a dose of 0.1, 1 and 10 mg/kg BW (body weight)/day tomato extract, respectively. Each group of mice was intraperitoneally infected with 107 cells/mL Plasmodium berghei. On the 8th day post infection, the mice were sacrificed and lymphocytes and macrophages were isolated and subsequently cultured. The expression levels of IL-12 and IFN-γ, as well as the macrophage phagocytosis index of the cells, were then determined. IL-12 levels were significantly different (p